(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Hyperlipidemia is emerging as an important cause of adverse health outcomes including cardiovascular complications, obesity, metabolic disorders, and infertility. A total of twenty-five (25) male albino Wistar rats were divided into five groups (n=5): Normal control, Hyperlipidemic control group which was administered (intra-peritoneal) with 0.2ml/10g body weight of egg yolk and then terminated after twenty-four (24) hours, Hyperlipidemic non-treated group which were administered with 0.2ml/10g body weight of egg yolk and were left throughout the treatment period. Hyperlipidemic low-dose treated group (administered 0.2ml/10g body weight of egg yolk, 800mg/kg body weight of methanolic extract of Citrullus lanatus seed-MECLS), and Hyperlipidemic high-dose treated group (administered 0.2ml/10g body weight of egg yolk, and 1600mg/kg body weight of MECLS). No significant change was observed in testosterone levels and sperm count across all groups. However, a statistically significant increase (P<0.05) in luteinizing hormone (LH) and follicle stimulating hormone (FSH) levels was observed in Hyperlipidemic non-treated and Hyperlipidemic low-dose treated group when compared to Normal Control Group. They also showed marked testicular damage and significantly decreased (P<0.05) sperm cell motility and significantly increased sperm cell abnormalities. Hyperlipidemic low and high dose groups exhibited moderate and complete regeneration of testicular histo-architecture respectively. Furthermore, high dose treated group showed a significant decrease in sperm count, motility, LH and FSH levels. This study suggests that MECLS dose dependently ameliorates testicular damage induced by hyperlipidemia but may affect sperm cell characteristics